2020
DOI: 10.1111/nyas.14348
|View full text |Cite
|
Sign up to set email alerts
|

Unique bone marrow blood vessels couple angiogenesis and osteogenesis in bone homeostasis and diseases

Abstract: Blood vessels serve as a versatile transport system and play crucial roles in organ development, regeneration, and stem cell behavior. In the skeletal system, certain capillaries support perivascular stem cells or osteoprogenitor cells and thereby regulate bone formation. Recent studies reported that a specialized capillary subtype, termed type H vessels, is shown to couple angiogenesis and osteogenesis in rodents and humans. They can be distinguished by specific cell surface markers, as the endothelial cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 90 publications
(120 reference statements)
1
17
0
Order By: Relevance
“…This is consistent with the finding that women suffering coronary endothelial dysfunction are at higher risk of developing osteoporosis than their normal counterparts [1]. Furthermore, substantial supply of blood to the bone reassures bone remodeling [11], creates a suitable microenvironment for growth factors and metabolites in fractured bone [9], reduces inflammation for bone healing [12] and couples osteogenesis and angiogenesis in bone homeostasis [13]. Alluding to these findings, it is evident that a clinically viable link exists between hormone levels, osteoporosis and endothelial dysfunction.…”
Section: Introductionsupporting
confidence: 84%
“…This is consistent with the finding that women suffering coronary endothelial dysfunction are at higher risk of developing osteoporosis than their normal counterparts [1]. Furthermore, substantial supply of blood to the bone reassures bone remodeling [11], creates a suitable microenvironment for growth factors and metabolites in fractured bone [9], reduces inflammation for bone healing [12] and couples osteogenesis and angiogenesis in bone homeostasis [13]. Alluding to these findings, it is evident that a clinically viable link exists between hormone levels, osteoporosis and endothelial dysfunction.…”
Section: Introductionsupporting
confidence: 84%
“…[46][47][48] Evidence has shown that the crosstalk between osteoblast or osteoclast lineage cells and type H ECs promotes subchondral angiogenesis and aggravates subchondral bone remodelling. [49][50][51] Type H ECs surrounded by osterix-expressing osteoprogenitors produce high levels of angiocrine factors (such as plateletderived growth factor (PDGF)-A, TGF-β1 and fibroblast growth factor (FGF)−1), stimulating survival, proliferation and differentiation of these osteoprogenitors to promote local bone formation. 52 53 Type H ECs intercommunicate via the intercellular Notch/delta-like protein 4 (DLL4) signalling pathway to induce the production of Noggin, 54 which stimulates the differentiation of osteoprogenitors surrounding vessels.…”
Section: Microstructural and Histopathological Alterations In Oa Subcmentioning
confidence: 99%
“…Type H vessels are a specialized subtype of capillary that expresses high levels of CD31 and endomucin, and these vessels are located near the growth plate in the metaphysis, the periosteum, and the endosteum of the diaphysis. Type H vessels are densely surrounded by osteoprogenitors [39] and aid in modulating osteoblasts, coupling osteogenesis to angiogenesis. There is also an embryonically expressed vessel termed Type E, with a similar expression pattern to type H vessels, but in mice they are highly expressed at E16.5 and then exhibit diminished expression by P28 [19] .…”
Section: Discussionmentioning
confidence: 99%